Kearifan Lokal dalam Mitigasi Bencana Gunung Api di Padukuhan Pangukrejo Pasca Erupsi 2010 - Puspita Dewi; Winarna (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2022)
Title: Local Wisdom in Volcanic Disaster Mitigation in Pangukrejo Village Post 2010 Eruption Merapi, as one of the active volcanoes in Indonesia, become a threat to the surrounding settlements. Especially large eruption that happened in the 2010 which created crater openings that increased the potential for eruptions leading to Pangukrejo Village, as one of it's area. On the other hand, Pangukrejo Village included in the Disaster-Prone Area III (KRB III) but refused to be relocated. After the 2010 eruption, people realized that they need not only local wisdom but also mitigation efforts by government. Until now, both local wisdom and disaster mitigation have worked together to increasing the preparedness of the people in this village to face future eruptions of Merapi. This study aims to identify local wisdom that still being carried out and worked together with disaster mitigation in Pangukrejo Village, which reviewed from the physical aspects, such as zone planning, early warning systems, and building design. The research use descriptive qualitative method with data analysis using content analysis technique and choosing respondents using purposive sampling technique. Based on the results of the research, it was finally found that there are the same meanings and interrelated key patterns that make local wisdom still being carried out and worked together with disaster mitigation.